Find the inverse function of function , and evaluate .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Method 1
Let y be the output of f ( x ) . The inverse function should therefore take in a y value and return the corresponding x value. Since y = 2 x + 5 x − 3 , and we want to find x in terms of y , we just need to change the subject of the function from y to x .
y ( 2 x + 5 ) = x − 3
2 x y + 5 y = x − 3
2 x y − x = − 3 − 5 y
x ( 2 y − 1 ) = − 3 − 5 y
x = 2 y − 1 − 3 − 5 y
Therefore f − 1 ( y ) = 2 y − 1 − 3 − 5 y . We now need to evaluate f − 1 ( 1 ) , so we substitute y = 1 into f − 1 ( y ) .
2 ( 1 ) − 1 − 3 − 5 ( 1 )
1 − 8 = − 8
Method 2
f − 1 ( 1 ) is equivalent to the output of f ( x ) , to which the answer is 1 . This means, we can substitute the output as 1 in the equation for function f .
1 = 2 x + 5 x − 3
2 x + 5 = x − 3
x = − 8